Purification and In Vitro Activity of Mitochondria Targeted Nitrogenase Cofactor Maturase NifB - Burén, Stefan; Jiang, Xi; López-Torrejón, Gema; Echavarri-Erasun, Carlos; Rubio, Luis M. (Frontiers in Plant Science, 2017)
Active NifB is a milestone in the process of engineering nitrogen fixing plants. NifB is an extremely O2-sensitive S-adenosyl methionine (SAM)–radical enzyme that provides the key metal cluster intermediate (NifB-co) for the biosyntheses of the active-site cofactors of all three types of nitrogenases. NifB and NifB-co are unique to diazotrophic organisms. In this work, we have expressed synthetic codon-optimized versions of NifB from the γ-proteobacterium Azotobacter vinelandii and the thermophilic methanogen Methanocaldococcus infernus in Saccharomyces cerevisiae and in Nicotiana benthamiana. NifB proteins were targeted to the mitochondria, where O2 consumption is high and bacterial-like [Fe−S] cluster assembly operates. In yeast, NifB proteins were co-expressed with NifU, NifS and FdxN proteins that are involved in NifB [Fe-S] cluster assembly and activity. The synthetic version of thermophilic NifB accumulated in soluble form within the yeast cell, while the A. vinelandii version appeared to form aggregates. Similarly, NifB from M. infernus was expressed at higher levels in leaves of Nicotiana benthamiana and accumulated as a soluble protein while A. vinelandii NifB was mainly associated with the non-soluble cell fraction. Soluble M. infernus NifB was purified from aerobically grown yeast and biochemically characterized. The purified protein was functional in the in vitro FeMo-co synthesis assay. This work presents the first active NifB protein purified from a eukaryotic cell, and highlights the importance of screening nif genes from different organisms in order to sort the best candidates to assemble a functional plant nitrogenase.